Problem-Based Learning Interactive Media in Elementary Indonesian Language Education: A Systematic Review (2020-2025) - Widi Astuti; Sri Sukasih; Panca Dewi Purwati; Nuni Widiarti; Bambang Subali (Papanda Publisher, 2026)
Indonesian language learning in elementary schools faces persistent challenges including low reading interest, writing difficulties, and monotonous conventional methods, necessitating innovative pedagogical interventions. This systematic literature review examines trends, contributions, and research gaps in problem-based learning (PBL)-based interactive media development for elementary Indonesian language learning during 2020-2025. Following PRISMA 2020 guidelines, four academic databases (Google Scholar, SINTA, Semantic Scholar, ERIC) were systematically searched, yielding 200 initial articles. Through rigorous four-stage screening applying PICOS framework criteria, 30 articles from nationally accredited (SINTA 1-3) and international (Scopus/ERIC-indexed) journals were selected for thematic content analysis. Analysis revealed progressive evolution from simple digital tools (Wordwall, Kahoot) toward sophisticated multimodal environments (Augmented Reality, Virtual Reality). Ninety percent of studies reported significant improvements in literacy competencies, particularly writing skills (40%) and reading comprehension (30%). ADDIE and 4D development models predominated (66.7%), demonstrating superior methodological rigor. Three distinct research clusters emerged: basic literacy development (2020-2021), critical and digital literacy (2022-2023), and creativity with technological adaptation (2024-2025). PBL-based interactive media integration effectively operationalizes constructivist learning principles, substantially enhancing student engagement and 21st-century literacy competencies. However, persistent infrastructure limitations, inadequate teacher TPACK competencies, and underrepresentation of speaking skill development constrain optimal implementation, requiring comprehensive policy support and sustained professional development interventions.